Orbital Eccrine Hidrocystoma - Marangoz, Deniz (Turk J Ophthalmol, 2016)
A 29-year-old female patient presented with a painless mass on her upper eyelid medially. She noticed the mass 4 years earlier and it had increased in size over time. She had no diplopia, eyelid swelling, skin lesion overlying the mass, or visual disturbances. On ocular examination, eye movements and funduscopy were normal. The mass was movable and painless with palpation. Magnetic resonance imaging with contrast showed a 12x8x7 mm well-circumscribed cystic lesion with no contrast dye appearance. Surgical removal was performed delicately and no capsular rupture occured. Pathological examination revealed an eccrine hidrocystoma. Our aim is to underline that eccrine hidrocystoma should be included in differential diagnosis of orbital masses.